Pepper seed in fistula-in-ano: a rare case report - Ideh, Stanley N.; Ekpeti, Azuka P.; Iweka, Reuben O.; Ideh, Bettyna U. (International Surgery Journal, 2025)
Anal fistula is a chronic connection between the anal canal and perianal skin. They are relatively common proctological cases and have been associated with foreign bodies. This case is being reported due to the unusual findings of pepper seed and to raise surgeons' awareness of such possibilities. We report a 52-year-old male who presented with complaints of recurrent swelling in the anal region of 8 years which was associated with itching and spontaneously ruptured with purulent discharge and faecal effluents. There was no associated history of anal trauma or insertion of foreign objects. He observed good perineal hygiene and there was no use of spices or herbal medication in anal region. No previous history of anal surgery. The Fistulogram showed a sinus tract with demonstrable communication with anal canal for which a diagnosis of fistula-in-ano was made. He had a fistulectomy with findings of two fistulous tracts at 11 o'clock, 12 o'clock positions, and critical examination of the excised tissue revealed two pepper seeds. Fistula-in-ano is a complication of perianal abscess in most cases. It results from inflammation of the anal crypts (pyogenic cryptitis) which is the early stage of the suppurative process. The retention of purulent effluent leads to its’ expansion into the various spaces adjacent to the rectum and anal canal. Despite reports of foreign bodies in the fistula tract, pepper seeds have yet to be reported to the best of our knowledge. Hence, we are reporting it. Fistula-in-ano is a relatively common proctological presentation and has been associated with complications from perianal abscesses and foreign bodies. However, the occurrence of pepper seed(s) is yet to be reported. This case is being reported due to the unusual findings and may be an avenue for further exploration of such possibilities.